Pelatihan dan Pengembangan Peningkatan Kompetensi Penulisan Karya Ilmiah Bagi Dosen Universitas Prima Kota Medan - Absah, Yeni; Situmorang, Syafrizal Helmi; Sembiring, Beby Karina F.; Gea, Saharman (Universitas Malikussaleh, 2024)
Writing scientific papers is a way to convey knowledge, thoughts and research results to the scientific community and the general public. Lecturers who have competence in writing scientific papers are able to produce quality writing, based on strong research methodology, in-depth analysis, and a good understanding of their field of science. Quality scientific work not only contributes to the development of knowledge, but also triggers discussion, debate and further development. A lecturer's ability to write scientific papers also has an impact on the academic reputation of the lecturer himself and the institution where he teaches. Lecturers who are active in publishing scientific work in leading journals or contributing to academic books will be recognized as authorities in their field. Universities and higher education institutions have an important role in supporting the development of lecturers' competence in writing scientific papers. Scientific writing training or workshops will help lecturers understand the scientific writing process, from planning, data collection, to presenting results. Apart from that, interdisciplinary collaboration and collaborative networks with fellow researchers will also help in overcoming obstacles and improving the quality of scientific work. To overcome various obstacles and problems with lecturers' competence in writing scientific papers, the solution offered to overcome these problems is to provide training and assistance in writing scientific papers.